Open Vehicle Routing Problem with Time Windows in a Real Case Application - Nouir, Rihem; Hamdi, Imen (2024 International Conference on Decision Aid Sciences and Applications (DASA), 2024)
The vehicle routing problem is a complex yet crucial issue for companies' logistical optimization. Commonly, it is one of the most interesting problem as it is encountred frequently in real life while subjecting to different constraints to optimize various criteria. In this paper, we are interested in the Open Vehicle Routing Problem (OVRP) with a homogeneous fleet of vehicles and time windows constraints. It is proved to be strongly NP-hard. We propose a Mixed Integer Linear Programming (MILP) which is runned by CPLEX solver to obtain optimal solution for small sized problems. However, for large sized instances, we develop an innovative K-means based-algorithm. Then, the computational results prove its performance by testing real world instances.